Determination of Particulate Matter Dispersion in Eastern Black Sea Region Using Geographical Information Systems - Kazım Onur Demirarslan; Halil Akıncı (Doğal Afetler ve Çevre Dergisi)
Factors like unplanned urbanization, transportation and industry in Eastern Black Sea cause significant adverse effects in this region. One of these effects is the air pollution. Air pollution reduces the life quality in cities and also it brings about many health problems. Especially, in winter, fossil fuels are used for the purpose of commercial heating and these fuels cause serious air pollution in the region. One of the important sources which may lead to air pollution in research area is coastal road of Black Sea. This road extends from borderline of Georgia to western Black Sea Region of Turkey and is an important route for transportation. The effects and dispersions of PM10 pollutant in the provinces of Artvin, Bayburt, Giresun, Gümüşhane, Ordu, Rize and Trabzon located along the Eastern Black Sea Region were investigated using maps generated by Geographic Information Systems (GIS). Data related to air quality was obtained from the hourly measurements of the stations used by the Ministry Environment and Urban Planning between 2010 and 2015. According to the study results, it was determined that, in specified date range, the concentrations of PM10 were high; in all seasons for Trabzon and Gümüşhane, in the summer, autumn and winter seasons for Bayburt and especially in the autumn for Ordu.